Project on Human Development in Chicago Neighborhoods (PHDCN): Caregiver-Subject Conflict Scale, Wave 2, 1997-2000 - Earls, Felton J. ([Verlag nicht ermittelbar], 2006)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Caregiver-Subject Conflict Scale (CSC). The CSC was administered to the primary caregiver (PC) of subjects belonging to Cohorts 0-15. This Wave 2 study was modified from the Wave 1 parent-child version of the Conflict Tactics Scale (PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): CONFLICT TACTICS SCALE FOR PARENT AND CHILD, WAVE 1, 1994-1997 [ICPSR 13584]) by adding items related to more positive forms of disciplinary tactics, modifying the response scale, and inquiring about tactics used not only by the PC, but by any adult household member. The CSC asked if any of several different ways of settling problems with the subject were used by any adult household member in the past year.